1988
DOI: 10.1159/000177423
|View full text |Cite
|
Sign up to set email alerts
|

Influence de divers types d&rsquo;ob&eacute;sit&eacute; exp&eacute;rimentale sur la r&eacute;sistance de la souris &agrave; &lcaron;infection par <i>Salmonella typh&iacute;muriu</i><i>m</i> et <i>Klebsiella pneumoniae</i>

Abstract: Resistance to infections inducing two types of immune response, humoral and cell-mediated, has been measured in mice after Salmonella typhimurium and Klebsiella pneumoniae inoculation; the animals exhibited different kinds of obesity: genetic, ob/ob and db/db mutants, induced by fat diet or gold thioglucose (aurothioglucose) injection (determining obesity of central origin). Klebsiella infection was aggravated in all types of obesity. Salmonella infection was aggravated in genetically diabetic and dietary-obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In basal conditions there was a severe defect in anti‐microbial activity in both SVF and macrophages from ob/ob mice. An immune deficiency has already been described in obesity both in humans and animal models (Conge et al, 1988; Stallone, 1994). The decrease in candidacidal activity of the macrophages from obese mice has to be related to the decrease in bactericidal capacity of mononuclear phagocytes described in humans (Chandra, 1980; Palmblad et al, 1980), although their phagocytic capacity was unchanged (Chandra, 1980).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In basal conditions there was a severe defect in anti‐microbial activity in both SVF and macrophages from ob/ob mice. An immune deficiency has already been described in obesity both in humans and animal models (Conge et al, 1988; Stallone, 1994). The decrease in candidacidal activity of the macrophages from obese mice has to be related to the decrease in bactericidal capacity of mononuclear phagocytes described in humans (Chandra, 1980; Palmblad et al, 1980), although their phagocytic capacity was unchanged (Chandra, 1980).…”
Section: Discussionmentioning
confidence: 94%
“…However, research in human obesity suggests that phagocytes may be particularly affected (Bray, 1985; Chandra, 1991; Stallone, 1994). In animals, differences in immune responsiveness have been described between mouse strains and between different types of obesity (Conge et al, 1981, 1988; Stallone, 1994), and recent findings demonstrate functional and phenotypic abnormalities in macrophages from Zucker rats (Plotkin et al, 1996) or ob/ob mice (Loffreda et al, 1998; Lee et al, 1999). According to the authors, these macrophage defects could be explained by leptin deficiency observed in ob/ob mice (Loffreda et al, 1998; Lee et al, 1999).…”
mentioning
confidence: 99%
“…There are now a number of reports demonstrating that leptin or leptin receptor deficiency disables host defense against bacterial infections (1215, 19, 3335). Unlike other models of leptin or leptin receptor deficiency, the l/l mouse is neither obese nor hyperglycemic and thus provides an excellent model for assessing the importance of distinct LepR mediated signaling events in host defense against bacterial infection in the absence of endocrine abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this inconsistency remain unclear. Studies in murine models of obesity have shown failure to contain both influenza (14, 15) and bacterial (16, 17) pneumonias with consequent lung injury and death. Subsequent work examining influenza has focused on the role of altered adaptive immune response in obesity (1821).…”
Section: Introductionmentioning
confidence: 99%